A SOCIOLINGUISTICS ANALYSIS OF ADRESSING TERM USED IN AISYAH: BIARKAN KAMI BERSAUDARA MOVIE - Syahidawati, Neneng Meilinda Nur; Parmawati, Aseptiana (PROJECT (Professional Journal of English Education), 2020)
The purpose of this research, namely analyzing  Aisyah : biarkan kami bersaudara movie to find out the type of addressing term used in this movie. This research uses descriptive qualitative method taken from the dialogue spoken by the characters in Aisyah : biarkan kami bersaudara movie. In this movie five addressing terms are found, namely the addressing term using name, addressing term using kinship name, addressing term using intimacy name, addressing term using respect name, and addressing term Using mockery name. The most commonly used term is addressing term using name.Keywords:  Adressing Term, Movie